2014
DOI: 10.4236/aim.2014.43019
|View full text |Cite
|
Sign up to set email alerts
|

The Optimization of <i>Aspergillus</i> sp. GM4 Tannase Production under Submerged Fermentation

Abstract: Tannase is a hydrolytic enzyme that is involved in the biodegradation of tannins and it has biotechnological potential in the pharmaceutical, chemical, food and beverage industries. Microorganisms, especially filamentous fungi, are important tannase producers. The aims of this work were to find a potential tannase producer and to improve the cultivation conditions. Three Aspergillus species (A. japonicus 246A, A. tamarii 3 and Aspergillus sp. GM4) were investigated in different culture media (Adams, Czapeck, K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…A positive coefficient indicated that the higher concentrations of the variable is best for increasing Cr(VI) removal and residual tannic acid, whereas negative values indicated the vice versa (Pulimi et al 2012 ). Mohan et al ( 2013 ); Costa Souza et al ( 2015 ) and Melo et al ( 2014 ) found TA significant for tannase production by Aspergillus sp. in Plackett–Burman study.…”
Section: Discussionmentioning
confidence: 97%
“…A positive coefficient indicated that the higher concentrations of the variable is best for increasing Cr(VI) removal and residual tannic acid, whereas negative values indicated the vice versa (Pulimi et al 2012 ). Mohan et al ( 2013 ); Costa Souza et al ( 2015 ) and Melo et al ( 2014 ) found TA significant for tannase production by Aspergillus sp. in Plackett–Burman study.…”
Section: Discussionmentioning
confidence: 97%
“…The Khanna medium was also used for tannase production by A. ochraceus [26], Aspergillus sp. [29] and A. japonicus 246A [30]. Other media also have been used for tannase production such as Czapeck medium for A. niger [31] and Mineral medium for A. fumigatus CAS21 [32].…”
Section: Resultsmentioning
confidence: 99%
“…The entire process of fermentation is divided into three parts, upstream, fermentation and downstream processes. The optimization of the factors at each individual step is important to understand the overall process; there are factors that can be varied in each of these steps that shall bring about the required change in the process (Kumar et al 2010;Irfan et al 2016;de Melo et al 2014). The upstream process involves the pre-treatment part, wherein the material and parameters are set for the process to run, it is the primary optimization section as most of the optimization parameters are to be decided and set at this stage so that the processing can be carried out smoothly, optimized parameters in this stage will make it easier for the overall process to run without much difficulty.…”
Section: Nature Inspired Optimization Techniquesmentioning
confidence: 99%
“…Most commonly used when second-order and higher surface response surface models are built and are most suitable for higher order parameter designs when physical as well as chemical parameters play a significant role in determining the output of any process, as the design works much better with higher parameter numbers and the influence of more number of parameters in case of SSF is higher than in the case of SmF, the CCD can be considered as an extension of the factorial and RSM techniques and so it has a better command over the parameters involved in the SSF processes (Karmakar and Ray 2011;de Melo et al 2014). Figure 3b gives a simple representation of the different systems that are available in establishing the optimum using the CCD technique where the individual factors are represented along the edges of the cube and the optimum result is at the center of the cube.…”
Section: Central Composite Design (Ccd)mentioning
confidence: 99%